1998
DOI: 10.1523/jneurosci.18-12-04656.1998
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CPP32-Like Proteases Rescues Axotomized Retinal Ganglion Cells from Secondary Cell DeathIn Vivo

Abstract: The majority of retinal ganglion cells (RGCs) degenerate and die after transection of the optic nerve (ON) in the adult rat. This secondary cell death can primarily be ascribed to apoptosis. Recent work strongly suggests a decisive role for a family of cysteine proteases, termed caspases, as mediators of neuronal apoptosis. In this study, we investigated whether activation of caspases contributes to delayed death of RGCs after axotomy. Intraocular application of various caspase inhibitors rescued up to 34% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
149
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(162 citation statements)
references
References 50 publications
12
149
0
1
Order By: Relevance
“…It has been shown that this retrograde cell death can be ascribed to apoptosis (Garcia-Valenzuela et al, 1994;Rabacchi et al, 1994;Isenmann et al, 1997). Caspase-3 (CPP32)-like protease has been identified as an important mediator of apoptotic RGC death in our experimental paradigm (Kermer et al, 1998(Kermer et al, , 1999b. Morphological changes common to apoptotic cells include cell shrinkage.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been shown that this retrograde cell death can be ascribed to apoptosis (Garcia-Valenzuela et al, 1994;Rabacchi et al, 1994;Isenmann et al, 1997). Caspase-3 (CPP32)-like protease has been identified as an important mediator of apoptotic RGC death in our experimental paradigm (Kermer et al, 1998(Kermer et al, , 1999b. Morphological changes common to apoptotic cells include cell shrinkage.…”
Section: Discussionmentioning
confidence: 97%
“…Surgical procedures have been described elsewhere (K löcker et al, 1997; Kermer et al, 1998). Briefly, adult female Sprague Dawley rats (200 -250 gm) purchased from Charles River Wiga (Sulzfeld, Germany) were anesthetized by intraperitoneal injection of chloral hydrate (0.42 gm / kg body weight).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…cAMP, through protein kinase A activation, augments the effects of growth factors by causing their receptors to translocate to the cell surface (Meyer-Franke et al, 1998), and similar effects are seen in vivo (Shen et al, 1999). Even in the absence of polypeptide growth factors, long-term survival can be maintained in vivo by overexpressing the anti-apoptotic protein Bcl-2 (Bonfanti et al, 1996) or by limiting caspase activity (Kermer et al, 1998). Enhanced survival by itself is insufficient to assure axon regeneration, however, because Bcl-2-overexpressing mice show almost no axon growth past the site of nerve injury (Chierzi et al, 1999).…”
mentioning
confidence: 99%
“…Cutting the rat optic nerve results in apoptotic cell death of more than 80% of the retinal ganglion cells, which are the only retinal cells projecting an axon into the optic nerve, 14 days after the lesion has been set. [17][18][19] In recent studies we have successfully used the intraocular injection of recombinant BDNF peptide along with free radical scavenger 20 and inhibitory peptides for caspases 21 to prevent apoptosis of RGCs. However, due to the short half-life of the peptides repeated injections were necessary, finally resulting in overall damage of the retina.…”
Section: Introductionmentioning
confidence: 99%